Progressive Islam and Islam Nusantara Value as Anti-Bullying Education Models in Indonesia - Halim Purnomo; Hisyam, Muhammad Hisyam Syafii (Journal of Islamic Communication and Counseling, 2026)
This study explores the integration of Progressive Islam values and the concept of Islam Nusantara as a foundation for anti-bullying education models in Indonesia. Using a systematic literature review method, this research analyzes how the progressive Islamic values developed by Muhammadiyah—emphasizing rahmah (compassion), 'adl (justice), and tajdid (renewal)—and the cultural approach of Islam Nusantara promoted by Nahdlatul Ulama—emphasizing tasamuh (tolerance), wasathiyyah (moderation), and musyawarah—can be synergistically integrated to build comprehensive anti-bullying education. The findings indicate that bullying in Indonesian education is a complex socio-cultural phenomenon requiring holistic intervention. The integration of both Islamic approaches offers a powerful framework encompassing curriculum, school culture, and systemic policy dimensions. Implementation faces contextual challenges, including rhetoric-practice gaps, limited teacher capacity, cultural resistance, and resource constraints. Success factors include macro-level policy support, strategic partnerships, student empowerment, and evidence-based approaches. This research contributes to the development of culturally and religiously contextualized anti-bullying education literature and offers a conceptual blueprint for Islamic schools in Indonesia.